Civil Rights and Liberties - Clairmont, Kimberly; Jeknic, Petar; Mason, Sarah R.; Metzdorf, Alexandria (Open textbook library., 2023)
This volume focuses on the constitutional doctrine and law in the areas of civil rights and liberties. It contains excerpts of landmark cases covering the first amendment, second amendment, fourteenth amendment and the right to privacy. The excerpts include the constitutional issues in these cases that are related to civil rights and liberties with other questions of law and dicta omitted.